SEARCH LIMIT RANGE RESOURCE BASED CONCEPT PRICE SHADOWS - Pratiwi Pratiwi; Susi Wagiyati. Skom. MM (Jurnal Sistem Informasi, 1998)
Operations Research terms first used by Mc. Bowdsey Closky and Trefthen inEngland in 1940 to conduct research on military operations. In line with thesuccessful implementation of the military field of Operations Research, the industrystarted paying attention to these areas, and has contributed towards solving theproblem Operations Research, such as the emergence of simplex method for solvinglinear programming problems. Simplex method is used to solve Linear Programmingproblems are greater than the second dimension in which way is through the stages(recalculated) that measures the same calculation is repeated until the optimalsolution is reached.One basic assumption is the assumption deterministc Linear Programming whichstates that the parameters contained in the Linear Programming model (especiallyresource constraints) is a definite constants. In practice these parameters is aprediction, so it does not cover the possible source of power can be changed. Thischange is based on the concept of shadow price represents the va lue of changes in theoptimum value (Z value or benefit in the case of combination products) for eachadditional one unit of a single resource. Because the added advantage applies only ifthe variable remains the optimum basis. So it needs to be calculated to the extent ofwhat resources can be changed without changing the variable base.